The Role of Autophagy in Chemical Proteasome Inhibition Model of Retinal Degeneration - Gunawan, Merry (Int J Mol Sci, 2021)
We recently demonstrated that chemical proteasome inhibition induced inner retinal degeneration, supporting the pivotal roles of the ubiquitin–proteasome system in retinal structural integrity maintenance. In this study, using beclin1-heterozygous (Becn1-Het) mice with autophagic dysfunction, we tested our hypothesis that autophagy could be a compensatory retinal protective mechanism for proteasomal impairment. Despite the reduced number of autophagosome, the ocular tissue morphology and intraocular pressure were normal. Surprisingly, Becn1-Het mice experienced the same extent of retinal degeneration as was observed in wild-type mice, following an intravitreal injection of a chemical proteasome inhibitor. Similarly, these mice equally responded to other chemical insults, including endoplasmic reticulum stress inducer, N-methyl-D-aspartate, and lipopolysaccharide. Interestingly, in cultured neuroblastoma cells, we found that the mammalian target of rapamycin-independent autophagy activators, lithium chloride and rilmenidine, rescued these cells against proteasome inhibition-induced death. These results suggest that Becn1-mediated autophagy is not an effective intrinsic protective mechanism for retinal damage induced by insults, including impaired proteasomal activity; furthermore, autophagic activation beyond normal levels is required to alleviate the cytotoxic effect of proteasomal inhibition. Further studies are underway to delineate the precise roles of different forms of autophagy, and investigate the effects of their activation in rescuing retinal neurons under various pathological conditions.